Oberonia sinica and O. pumilum var. rotundum are new synonyms of O. insularis (Orchidaceae, Malaxideae) - Li, Yu Ling; Tong, Yi; Ye, Wen; Chen, Hong Feng; Xing, Fu Wu; Yi, Qi Fei (Phytotaxa, 2017)
Based on examinations of herbarium specimens, reviews of pertinent literature, and observations on living plants, the Chinese species previously placed in the genus Hippeophyllum are revisited. H. sinicum and Oberonia pumilum var. rotundum are reduced to synonymies of O. insularis. Nomenclature problems of the names Hippeophyllum pumilum and Oberonia pumila are also discussed.